KOMUNIKASI INTERPERSONAL BERPERSPEKTIF BIMBINGAN DAN KONSELING DALAM MEMBANGUN HUBUNGAN KERJA NYAMAN PADA DIVISI LAPANGAN - Syifa Abdurrohim; Siti Napisah; Fajar Wahyu Prasetyo (CV. Lafadz Jaya, 2026)
This study is grounded in the importance of interpersonal communication in building comfortable working relationships in a field division that operates under time pressure, technical accuracy, and changing project conditions. The purpose of this study was to describe the application of interpersonal communication from the perspective of guidance and counseling and to identify the barriers experienced by employees of the Field Division of PT. Deden Decor Indonesia, Tangerang Office, Banten Province. This research employed a qualitative case study approach. The participants consisted of one field coordinator and four field administrators selected because of their direct involvement in daily work communication. Data were collected through observation, in-depth interviews, and documentation study, then analyzed through data reduction, data display, and conclusion drawing. The findings show that interpersonal communication is practiced through work coordination, openness, empathy, support, positive attitude, equality, and shared meaning of comfortable working relationships. However, the implementation is not fully consistent because it is still influenced by time pressure, brief instructions, psychological barriers, technical terms, field conditions, and media-related disturbances. Guidance and counseling principles can strengthen workplace communication through acceptance, active listening, clarification, empathy, and more constructive feedback.